The concretion of an illegality The administrative character of the Asambleas Departamentales (2003)
The author makes a detailed explanation of the impossibility of Departmental Assemblies to make taxes, due to the fact that this is an exclusive right of Congress. He concretely attacks the disposition that fixes a tax on Boyacá telephone users in benefit of sports in the area.